Expert Recommendations for Health Literacy Policies addressing Children and Adolescents. (30th September 2020) - Okan, O; Corsmeier, M; Sørensen, K; Bauer, U
Abstract: Background: There is an on-going and a well observable uptake of health literacy in the national and international agenda-setting pertaining to the development of new policy strategies to address the issue of promoting health literacy in whole societies. Therefore, the aim of this research is to analyse those policies on how they address children and develop recommendations for future policies. Methods: Policy documents on national levels, published by February 2019 were retrieved using a two-pronged strategy: (1) systematic review methods (database and online search) and (2) expert consultation. Based on a SWOT analysis of these policies, an interview guide was developed and policy experts (N = 63) from 46 countries across the world were interviewed. Based on the qualitative analysis, a Delphi Study was developed to gather expert comments and validation. Results: The search has identified 26 policies in 19 countries including case-laws and enacted statues, governmental strategies, polices driven by national key experts, and educational policies. The content of these informed the interview guide. The initial analysis of the interviews led to several recommendations pertaining to schools and the education sector, including principals, teachers and whole-school approaches, characteristics of different settings, such as policy, education and administration, economic perspectives, and the need for research and evidence in order to inform future strategies. Conclusions: The results will be compiled into a recommendation report and a policy brief. In addition, those will be translated into other languages to share with the countries of the experts who participated in this project. While almost all policies address children somehow, several limitations make it difficult to evaluate the quality of the different policies. To secure and sustain more effective, child-focused policies, current knowledge gaps regarding research on children`s health literacy should be addressed.